Analysis of the concept of schikking as an alternative in the strategy for recovering state financial or economic losses - Syam, Asmadi; Din, Mohd; Bintang, Sanusi; M. Gaussyah; Irsan, Muhammad (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: The main issue in handling cases in the economic field is the recovery of the state's financial losses or the country's economy. This is due to the orientation of law enforcement, which always focuses on imposing imprisonment as a deterrent. As a result, fines that are imposed are often substituted with imprisonment. The criminal justice process, which ultimately leads to imprisonment, is considered ineffective and incurs high costs. Through the authority of schikking, it is considered as one of the alternative solutions. However, in practice, it still generates various reactions, including assumptions that it does not effectively deter perpetrators from committing crimes. Purpose/Study Objectives: This research aims to examine and explain the perspective of schikking in handling economic criminal acts. Through the imposition of schikking, can financial losses or the state's economy be effectively and efficiently restored. Design/Methodology/Approach: The research method used is normative juridical research, a type of legal research that examines the systematics of law, identifying key concepts in law, and analyzing prevailing norms and principles in legal science. Findings: The research findings indicate that the concept of schikking views economic crimes as the cause of economic disruption in the country, so the prosecution must prioritize the recovery of state losses. As one of the sentencing systems and part of the attorney general's opportunity, schikking can be applied to crimes that have a broad impact on the country's economy. The implementation of schikking is considered effective and efficient in reducing state expenditures, taking into account the costs and benefits of handling economic cases. Additionally, schikking provides a mutually beneficial solution for the parties by giving the perpetrator an opportunity to constructively demonstrate their capacity and qualities. Schikking does not completely eliminate the element of deterrence, but rather simplifies the criminal justice system by offering a more efficient and adaptable solution, without sacrificing the core goals of law enforcement, restoring economic losses, and ensuring substantive justice. Paper Type: Research Article.